Load Dynamic Performance Sensitivity Analysis with respect to End-Use Motor Characteristics and Distribution Feeder Networks - Srinivasan, Rahul (My University, 2010)
Motor dynamics sensitivity analysis with respect to end-use motor characteristics (inertia, load torque profile, electrical parameters) is presented in this thesis. Mechanical data of motors play a very important role in determining motor dynamics, sometimes even overshadowing the effect of electrical parameters. This work provides results that establish the importance of motor mechanical characteristics such as inertia (H) and load torque profile (D) while examining motor load dynamics. Distribution system model equivalencing and load dynamic performance (as seen from the power grid) sensitivity analysis with respect to the distribution (feeders and transformers) network is another key topic covered in this thesis. It is impractical to represent the complete distribution system for analysis and hence it is of paramount importance to construct an equivalent distribution system model which contains all the important details of the system but at the same time is not overtly complex. Five such models are proposed in this work. Furthermore, sensitivity analysis with respect to the distribution network is performed in order to convey the significance of the distribution network in studying load dynamic performance.